2013
DOI: 10.4049/jimmunol.1300027
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Neurons Regulate Monocyte Trafficking and Mortality during Gram-Negative Peritonitis in Mice

Abstract: Effective host defense requires a robust, yet self-limited response to pathogens. A poorly calibrated response can lead to either bacterial dissemination due to insufficient inflammation or to organ injury due to excessive inflammation. Recent evidence suggests that the cholinergic anti-inflammatory reflex helps calibrate the immune response. However, the influence of peripheral noradrenergic neurons, which are primarily sympathetic neurons, in regulating immunity remains incompletely characterized. Using a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Previous studies have shown that inflammatory monocytes are involved in controlling inflammation in gram-negative pneumonia and abdominal infections. 8,9,[38][39][40][41][42] A lower number of inflammatory monocytes has been associated with increased lesions in the lung and in the intestinal lamina propria. 8,9,38,41 Other studies have shown that the CX3CR1/ CX3CL1 axis is involved in the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inflammatory monocytes are involved in controlling inflammation in gram-negative pneumonia and abdominal infections. 8,9,[38][39][40][41][42] A lower number of inflammatory monocytes has been associated with increased lesions in the lung and in the intestinal lamina propria. 8,9,38,41 Other studies have shown that the CX3CR1/ CX3CL1 axis is involved in the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be cautioned that extra-myeloid effects of systemic sympathectomy could also play a role. For example, the spleen functions as a major reservoir for inflammatory monocytes whose release requires angiotensin signaling through the AT-1 receptor and is controlled by noradrenergic neurons [75, 76]. Consequently, catecholamine depletion has been found to enhance monocyte recruitment to sites of bacterial infection [76], presumably due to exacerbated splenic release rather than altered myelopoiesis.…”
Section: Role Of the Pns In The Development Deployment And Homeostamentioning
confidence: 99%
“…For example, the spleen functions as a major reservoir for inflammatory monocytes whose release requires angiotensin signaling through the AT-1 receptor and is controlled by noradrenergic neurons [75, 76]. Consequently, catecholamine depletion has been found to enhance monocyte recruitment to sites of bacterial infection [76], presumably due to exacerbated splenic release rather than altered myelopoiesis. Furthermore, there is also a pool of inflammatory monocytes in the BM that can be released upon TLR sensing by MSCs which induces MCP-1 (CCL2) expression and CCR2-dependent monocyte emigration [77].…”
Section: Role Of the Pns In The Development Deployment And Homeostamentioning
confidence: 99%
“…Time lapse analysis showed that monocytes recruited in the infarcted heart are derived first from the circulating blood then from the spleen 3 . In mouse models of peritoneal inflammation 4 , intestinal inflammation 5 , and spinal cord injury 6 , three independent groups found that the spleen is a significant source of infiltrating monocytes. On the other hand, many published studies using bone marrow chimeras have established the contribution of bone marrow-derived Ly6Chi monocytes in models of tissue injury 7, 8, 9 .…”
Section: The Case For Skepticism and The Need For Extensive Validatiomentioning
confidence: 99%
“…The involvement of mononuclear splenocytes in chronic post-infarction heart failure suggests that the molecular signals involved in their mobilization may be independent of the acute inflammatory response. Neurohumoral angiotensin II-mediated signaling may be responsible for sustained mobilization of splenic monocytes following myocardial infarction 1, 12 ; sympathetic activation may also contribute to egress of pro-inflammatory splenocytes 4 . Dissecting the pathways that govern recruitment of mononuclear cell subsets from the bone marrow and from extramedullary sources, and understanding temporal and spatial aspects of their trafficking is crucial to gain both pathophysiologic insights and therapeutically relevant information.…”
Section: The Need For Exploration Of Mechanisms Mobilizing the Splenimentioning
confidence: 99%